Post-Processing of Complex SLM Parts by Barrel Finishing - Alberto Boschetto; Luana Bottini; Luciano Macera; Francesco Veniali (Applied Sciences, 2020)
Selective laser melting (SLM) enables the production of metal complex shapes that are difficult or impossible to obtain with conventional production processes. However, the attainable surface quality is insufficient for most applications; thus, a secondary finishing is frequently required. Barrel finishing is an interesting candidate but is often applied without consistent criteria aimed at finding processing parameters. This work presents a methodology based on Bagnold number evaluation and bed behavior diagram, developed on experimental apparatus with different charges and process parameters. The experimentation on an industrial machine and the profilometric analysis allowed the identification of appropriate process parameters and charge media for finishing the investigated materials (Ti6Al4V and Inconel718). Two case studies, characterized by complex shapes, were considered, and consistent surface measures allowed understanding the capability of the technology.